Analysis Quality of Service using Service Performance and Importance Performance Analysis Method at Community Health Center - Della Puspita, Fannysah; Enny Aryanny (The Indonesian Journal of Computer Science, 2024)
Community health center is a health services in Indonesia that aims to organize first-level public health efforts. The current condition observed in level one health centers in Indonesia relates to the services provided. A large portion of patients who have experienced the services express dissatisfaction with the level of service provided. This research aims  to determine the quality of service in community health center and provide advices to improve the quality of health center services. The method used in this research is the Servperf method and Importance Performance Analysis. Based on research with the service performance method, the mean performance level is 3,39 and the mean importance level is 4,38. Meanwhile, the Importance Performance Analysis obtained the level of conformity between performance and importance is 77,49% with seven atrributes of service quality dimensions that enter quadrant I and are the top priority for improvement. The proposed improvements are made to improve the quality of health center services in the future by adjusting the main priority attributes of improvements to the Importance Performance Analysis diagram.